Alexandra Munoz-Cordova: capstone - Munoz-Cordova, Alexandra, artist (Colorado State University. Libraries, 2025)
The artist's statement: As a first-generation Latina, I have overcome many challenges that have made me the artist I am today. My work in Graphic Design has been a display of those efforts and combines illustration and typography to showcase my perception of assigned themes and topics. My experiences and background are a display of who I am in my art. They are an upbringing of my efforts even if they don't directly speak to my Mexican identity. My diverse background is something I aspire to use as I continue to cultivate verbal, written and interpersonal skills both fluently in English and Spanish. My work is a direct showcase of not only my efforts but of the efforts of my mother and father who came here with nothing but still gave me everything. They left their families, their homes and learned a new language to give my sister and I the opportunity for a better future. I want to honor their sacrifices by taking the first step in breaking this generational chain of pursuing higher education. My parents will always be my greatest influence in everything I do, and I will do everything in my power to do good by them. And that for me is using my art as representation and as a voice for them and myself. For whenever I can't speak, I can create art to be my voice.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design